PENGEMBANGAN MECHANIC COURT WASIT BOLABASKET MENGGUNAKAN 4 ORANG - Atha, Muhammad Dany (Journal of Sport Coaching and Physical Education, 2017)
The Problem of this research is "how is the result of the MechanicCourtDevelopment of Bolabasket Referee Using 4 People in the IKK bolabasket of PKLO UNNES?", With the aim of developing mechancic court 4 bolabasket referee on basketball student of PKLO UNNES.This research uses development research method, namely: (1) preliminary research,information gathering and needs analysis, (2) initial product development in book form, (3) evaluation of three bolabasket coaches, (4) small group test(8 students) , (5) revision of the final product, (8) the formulation of the video script, (9) the final product of the form book and VCD. The research instruments include sample evaluation sheets, and arbitration expert questionnaires.Based on the result of the research, it is concluded that the development of Mechanic Court4 bolabasket referee on basketball student of PKLO UNNES can be used and very good. The results of this study can be used as an alternative to minimize referee errors in decision making.